ALAT PERMAINAN EDUKATIF “GUESS OUR GALAXY” UNTUK MELATIH KEMAMPUAN MOTORIK HALUS, DAYA INGAT, DAN KOGNITIF PADA SISWA PAUD - Dzulkifli, Dzulkifli; arumsari, andini dwi; Maulidiyah, Ummi Masrufah (Universitas Narotama, 2024)
Guess Our galaxy is an Educational Game Tool that was created to help Early Childhood to train basic skills in cognitive, memory, and cognitive. This research uses an experimental research type with a qualitative descriptive approach. Data collection techniques used in this study were observation and interviews with educators. This research was conducted at TK Aisyiyah 20 Kreatif Surabaya which is located on JL. Baratajaya VII/17 Surabaya, Baratajaya, Kec. Gubeng, City of Surabaya Prov. East Java. The subjects in this study were 32 students who were divided into 2 classes, namely the Rabit class with 18 students and the Tiger class with 18 students. From 32 subjects we took 2 students for further observation. Guess Our Galaxy has several stages in learning that present materials, quizzes, and practices that are expected to help train students' cognitive, memory, and fine motor skills. Educational Game Tools that have been given to the subject can be said to have succeeded in making students more interested in learning and arousing students' curiosity. The results of research conducted by researchers show that the educational game Guess Our Galaxy can help train the subject's cognitive, memory, and motor skills. Keywords: Educational game tools, cognitive ability, memory, and fine motor skills